"Gwiezdne wojny" - efekt bumerangowy [„Star Wars” - boomerang effect] - Niewińska, Jolanta (Biuletyn Edukacji Medialnej [Media Education Bulletin], 2019)
The understanding of good by a man who grew up in the “gutter” among juvenile gangs is distorted. It is not surprising then that Han Solo did not become a Jedi knight. However, can a young reader of “The Great Escape” from “Star Wars” reason this out? Media education is indispensable here, so that by analysing the content of the book and its context throughout the saga, we can come to conclusions that many would see as opposite to those intended by the author. So what is this boomerang effect?
https://katalog.adlr.link/Record/ai-53-762185